2000
DOI: 10.1021/je000084r
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Anthracene in Ternary 1,4-Dioxane + Alcohol + Cyclohexane Solvent Mixtures at 298.15 K

Abstract: Experimental solubilities are reported for anthracene dissolved in ternary 1,4-dioxane + 1-propanol + cyclohexane, 1,4-dioxane + 2-propanol + cyclohexane, 1,4-dioxane + 1-butanol + cyclohexane, 1,4-dioxane + 2-butanol + cyclohexane, and 1,4-dioxane + 2-methyl-1-propanol + cyclohexane solvent mixtures at 25°C and atmospheric pressure. Nineteen compositions were studied for each of the five solvent systems. Results of these measurements are used to test the predictive ability of the ternary solvent form of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…16 : initial mole fraction of component 2 in the binary solvent mixture; c 1 : molar solubility of the solute.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…16 : initial mole fraction of component 2 in the binary solvent mixture; c 1 : molar solubility of the solute.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…Molar concentrations were determined by spectrophotometric measurements at 356 nm. Pribyla et al [12][13][14][15][17][18][19][20][21] reported the solubility of anthracene in ternary alkane + 1,1′-oxybisbutane + alcohol, alkane + 2-methoxy-2-methylpropane + alcohol, and alkane + 1,4-dioxane + alcohol solvent mixtures at 298.15 K. Three alkane cosolvents: heptane (a linear alkane), cyclohexane (a cycloalkane), and 2,2,4-trimethylpentane (a highly branched alkane) and five alcohol cosolvents (1-propanol, 2-propanol, 1-butanol, 2-butanol, and 2-methyl-1-propanol) were studied. There has only been a single experimental determination for the solubility of anthracene in each of the ternary solvent systems studied.…”
Section: Auxiliary Informationmentioning
confidence: 99%
“…Currently, the most generalised version of the model is referred to as the Jouyban-Acree model [9,10]. To date, Equation (1) has been shown to provide accurate predictions for the solubility of anthracene dissolved in ternary alkane þ alkane þ alcohol [1,2], ternary alkane þ alcohol þ alcohol [3][4][5][6][7][8]11], ternary alkane þ ether þ alcohol [12][13][14][15][16][17][18][19][20], ternary alkoxyalcohol þ alkane þ alcohol [21], ternary alkoxyalcohol þ alcohol þ alcohol [22] and ternary alkoxyalcohol þ alkane þ alkane [23] solvent mixtures. Differences between predicted and observed values were less than 5% for the studied ternary solvent systems.…”
Section: Introductionmentioning
confidence: 99%